Agnikarma - Understanding the process from Past to the Present - Aditya Sharma; Neha Chauhan; P. Hemantha Kumar; Suman Sharma; Lokendra Pahadiya (International Journal of Ayurveda and Pharma Research, 2023)
Throughout human history, medical practices have evolved and adapted to the prevailing knowledge, culture, and technology of their time. One such ancient medical technique that holds a significant place in history is "Agnikarma," a fire-based therapeutic intervention. Originating in civilizations such as India, China, Greece, and Egypt, Agnikarma’s evolution and significance are explored within their cultural and medical contexts. Its origins are traced to ancient medical texts, including the "Sushruta Samhita" and the "Huangdi Neijing," which document its application in Ayurvedic and Traditional Chinese Medicine (TCM), respectively. Agnikarma’s role in treating a wide array of conditions, from pain relief to chronic ailments, is examined, reflecting its diverse applications across cultures. Agnikarma involves the application of heat to specific points on the body using a variety of instruments, such as metal rods, needles, and cow dung cakes. By stimulating blood circulation and promoting the body’s natural healing process, Agnikarma has been used to address conditions ranging from musculoskeletal pain to skin disorders. An attempt is made using this article to review how the process started from being worshipped like God to a therapeutic procedure, the step-by-step development. This review article explores the historical origins and contemporary use of Agnikarma therapy. The article also discusses the future directions for the research and development of this ancient healing technique. In essence, this historical review illuminates Agnikarma’s cultural significance, medical impact, and role in shaping the trajectory of medical practices through time.